Developing a short form of Oral Health Impact Profile (OHIP) for dental aesthetics: OHIP-aesthetic - Wong AHH, Cheung CS, McGrath C. (Blackwell Synergy, 2007)
To develop and evaluate shortened forms of the Oral Health Impact Profile (OHIP) for discriminating dental aesthetics problems and evaluating dental aesthetic outcomes